2016
DOI: 10.7566/jpsj.85.083705
|View full text |Cite
|
Sign up to set email alerts
|

Hall Effect in the Abrikosov Lattice of Type-II Superconductors

Abstract: We study vortex charging caused by the Lorentz force on supercurrent based on the augmented quasiclassical equa- tions of superconductivity. Our numerical study on an s-wave vortex lattice in the range $H_{{\rm{c}}1} < H < H_{{\rm{c}}2}$ reveals that each vortex core with a single flux quantum also accumulates charge due to the circulating supercurrent and has a Hall voltage across the core. The field dependence of the charge density at the core center is well described by $H(H_{{\rm{c}}2}-H)$ with a peak near… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
22
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 39 publications
5
22
2
Order By: Relevance
“…3) As the magnetic field is increased further, the vortex lattice symmetry generally starts to affect the charge distribution owing to the overlapping of vortices. 1) We observe the effect of overlapping clearly in Fig. 4 as compared with in Fig.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…3) As the magnetic field is increased further, the vortex lattice symmetry generally starts to affect the charge distribution owing to the overlapping of vortices. 1) We observe the effect of overlapping clearly in Fig. 4 as compared with in Fig.…”
mentioning
confidence: 65%
“…It was shown previously 1) on the basis of a microscopic theory 2,3) that the vortex-core charge accumulated by the Lorentz force on supercurrents exhibits a characteristic magneticfield dependence in two-dimensional s-wave superconductors. Specifically, the charge density at the core center ρ 0 approximately obeys ρ 0 (H) ∝ H(H c2 − H) owing to the competition between the increasing magnetic field H and decreasing pair potential (H c2 : upper critical field).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, our previous works have shown that the charge accumulation by the Lorentz force in the core is strongly enhanced compared with that of an isolated vortex as the external magnetic field increases from a lower critical field. 37,38) Thus, the contribution of the Lorentz force to the core charge may become dominant over the contributions of other forces in finite magnetic fields. Hence, we should study the magnetic-field dependence of the vortex-core charging due to the three forces by solving these augmented Eilenberger equations with three forces for the vortex lattice system.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is worth noting that ρ(0) has been shown to have a strong magnetic-field dependence with a peak structure and can be enhanced significantly over the value of an isolated vortex as the magnetic field is increased. 7,8) Hence, it is not appropriate to conclude that the Lorentz-force contribution is negligible in all cases.…”
mentioning
confidence: 99%